“They were the source and the fulfilment, and man was the fruit of their love”: a personalist investigation into the traces of the “Parable of the Prodigal Son” in Michael David O’Brien’s “The Father’s Tale” - de Oliveira Casemiro Pereira de Amorim, Victor Hugo; Rodovalho Amaral, Vítor (Cadernos de Pós-Graduação em Letras, 2025)
This paper applies the philosophies of Stein (2003), Berdyaev (1944) and Solovyov (1948) to the analysis of O’Brien’s novel “The Father’s Tale” (2011), whose main intertext is the “Parable of the Prodigal Son”. Using Stein’s ideas, we investigate the innate dignity of the human person within the narrative. In turn, Berdyaev’s perspective was seen as shedding light on the character’s moral journey. Solovyov, finally, offers an understanding of unconditional love as a transformative force. By emphasizing the contemporary relevance of the authors’ ideas in understanding dignity, human freedom and the divine aspect of human love, this study therefore contributes to the dialogue between literature and philosophy.